ANALISIS KELAIKAN FUNGSI JALAN PADA RUAS JALAN BUNDARAN PESAWAT KE LAMPU MERAH PASAR BARU - Soeparyanto, Try Sugiyarto; Syah Nuhun, Ridwan; Alamsyah, Sahrul; Minsi, Salfin Hartani; Dzariat, La ode (JURNAL TEKNIK SIPIL CENDEKIA (JTSC), 2024)
The purpose of this study is to analyze the feasibility of road functions on the Airplane Roundabout Road to Pasar Baru Red Light. The data analysis in this study is ULFJ analysis and Road Function Feasibility Administration Analysis. The research results indicate that (1) the analysis of ULFJ, overall the section from Bundaran Pesawat to Lampu Merah Pasar Baru falls into the category of "conditionally functional with recommendations (LS)" where the road section has partially met the technical requirements of LFJ; (2) the analysis results for road suitability testing with administrative requirements are as follows: (a) The Study Location is deemed suitable as a Secondary Arterial Road class within the City Road status; (b) The available land area for the reviewed road section meets the requirements for road design, but RUMIJA ownership documents are not yet available; (c) Traffic signs, orders, and prohibitions are already appropriate but eight signs are still needed for intersection requirements; (d) Administrative documents such as Environmental Impact Assessment (EIA) documents (DELH / DPLH) for the year 2019 and road ledger documents are available at the technical agency, but need updating; and (3) Spatially, the construction of the road from Bundaran Pesawat to Lampu Merah Pasar Baru can improve mobility, create employment opportunities, and boost economic growth.